Liberating Women From Patriarchal-Colonial Reasoning: Vandana Shiva and amina wadud's Proposition on God and Nature - Yazid Imam Bustomi (Elkuator Research and Publication, 2025)
This study critically examines the construction of patriarchal culture in both religious and ecological spheres, shaped by distorted interpretations of religious teachings and maldevelopment in the environment. It delves into the thoughts of amina wadud and Vandana Shiva, analyzing the impact of colonialism in perpetuating women’s marginalization in the public sphere and the need for decolonization. Employing a qualitative and library research approach, this research highlights key findings on gender decolonization within the contexts of religion and ecology. Firstly, male-dominated interpretations of sacred texts should incorporate women’s experiences to avoid bias and conflict, including patriarchal prejudices against humans and the environment. Secondly, women must have equal access to natural resource management, as their sustainable practices contrast with the exploitative modern management practices. Lastly, to achieve a just social order, women should be trusted and empowered to play active roles in all areas of life, challenging patriarchal assumptions. By providing a theoretical framework for liberating women from patriarchal colonial legacies, this research makes a meaningful contribution to the discourse on gender decolonization.